Effect of dispersion agent on the properties of water-absorption Resin in inverse suspension polymerization - XU Wei-liang (浙江大学学报. 农业与生命科学版, 2000)
A high water absorption polyacrylic acid resin was obtained using inverse suspension polymerization. Its effects on the physical properties and water absorption ability were studied with different dispersion agents and amounts, mixed dispersion agents and antiadhesion agents.